PENGARUH PEMBIAYAAN MUDHARABAH, PEMBIAYAAN MUSYARAKAH, DAN PEMBIAYAAN MURABAHAH TERHADAP PROFITABILITAS PADA BANK SYARIAH MANIDIRI DAN BANK MUAMALAT INDONESIA (Studi pada Bank Umum Syariah Yang terdaftar di Bank Indonesia Periode Triwulan I 2007- Triwulan IV 2014) - Sari, Mulia; Afif, M Nur (JURNAL AKUNIDA, 2016)
This study aimed to analyze the effect of financing, Musharaka financing and murabaha financing to profitability. This study uses return on assets (ROA) as an indicator of bank profitability. The population was Islamic Banks (BUS) which is registered in Bank Indonesia in the first quarter of 2007 - the fourth quarter of 2014. The sample in this study using purposive sampling technique. The results showed that the simultaneous effect of financing, Musharaka financing and murabaha financing to the profitability of 17.8%, while the remaining 82.2% is explained by other variables outside the model. That is, that the value of the contribution the effect of financing, Musharaka financing and murabaha financing to the profitability of 17.8% and the remaining 82.2% is influenced by other variables. Partially, the variable of financing and Musharaka financing significant effect on profitability, with a coefficient of amounting to 2,651 and 2,079 to the value of 0,010 and 0,042 t significance (significance t <0.05). While variable murabaha financing a significant and negative impact on profitability, with a coefficient of -3.593 with a significance value of 0.001 <0.05.Keywords: mudaraba, musharaka, murabaha, profitability